Proposal for geomorphological mapping of debris-covered and rock glaciers and its application to Tröllaskagi Peninsula (Northern Iceland). Issue 2 (13th November 2018) - Tanarro, Luis M.; Palacios, David; Zamorano, José J.; Andrés, Nuria
ABSTRACT: This work defends and applies a new proposal for mapping debris-covered glaciers and rock glaciers. This proposal combines highly accurate traditional methods, such as manual geomorphological photointerpretation, with novel digital techniques. The new methodological strategy applies rendering and lighting tools from Computer-Aided Design platforms and uses graphic design from Desktop Publishing Programs, to improve the geovisualization of geomorphological maps. This combination was applied to the debris-covered glacier and a set of rock glaciers located on the Tröllaskagi peninsula (northern Iceland). The result is a 1:4, 500 scale geomorphological map of 16 km 2, which for the first time maps the features that differentiate the debris-covered glacier from rock glaciers, as well as genetically different units within each formation and a long series of landforms characteristic of different processes. This map thus becomes a very useful tool in the evolutionary study of these formations in relation to the impact of climate change.